2021
DOI: 10.3390/ijerph18168660
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Evaluation of Alternative Time-Series Models for COVID-19 Forecasting in Saudi Arabia

Abstract: COVID-19 is a disease-causing coronavirus strain that emerged in December 2019 that led to an ongoing global pandemic. The ability to anticipate the pandemic’s path is critical. This is important in order to determine how to combat and track its spread. COVID-19 data is an example of time-series data where several methods can be applied for forecasting. Although various time-series forecasting models are available, it is difficult to draw broad theoretical conclusions regarding their relative merits. This pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 38 publications
0
6
0
1
Order By: Relevance
“…Because the data for each age structure fluctuated highly (see Fig. 1 ), we did preprocessing on the raw real data by using smoothing method, as in ( Demongeot et al., 2020 ), ( Al-Turaiki et al., 2021 ) and ( Zhao et al., 2021 ). Here, we used the smoothdata function with a Gaussian method to smooth the data, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because the data for each age structure fluctuated highly (see Fig. 1 ), we did preprocessing on the raw real data by using smoothing method, as in ( Demongeot et al., 2020 ), ( Al-Turaiki et al., 2021 ) and ( Zhao et al., 2021 ). Here, we used the smoothdata function with a Gaussian method to smooth the data, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Seperti yang dijelaskan dalam Al-Turaiki, et al [8], metode Holt-Winters telah diusulkan oleh Holt [9] dan Nurhamidah [10], menggunakan rata-rata bergerak tertimbang eksponensial yang diperlukan untuk penyesuaian musiman rata-rata (trend) dan musiman. Metode ini memiliki dua variasi dengan empat persamaan: satu persamaan prakiraan dan tiga persamaan smoothing.…”
Section: Model Holt-wintersunclassified
“…In which the researchers concluded that the study helps the teacher and the student to improve the student's grades. This paper [8] provided an empirical evaluation of several time series models for predicting COVID-19 cases, recovery, and mortality in KSA. Models were trained using self-regressive integrated moving average, exponential smoothing, cube slice, Holt simple exponential smoothing, and Holt winters.…”
Section: Review Of Related Workmentioning
confidence: 99%